Unilateral Discomfort Increases the Use of Contralateral Side during Sit-to-Stand Transfer. (26th April 2017) - Oludare, Simisola O.; Ma, Charlie C.; Aruin, Alexander S.
Abstract : Individuals with unilateral impairment perform symmetrical movements asymmetrically. Restoring symmetry of movements is an important goal of rehabilitation. The aim of the study was to evaluate the effect of using discomfort-inducing devices on movement symmetry. Fifteen healthy individuals performed the sit-to-stand (STS) maneuver using devices inducing unilateral discomfort under the left sole and left thigh or right sole and right thigh and without them. 3D body kinematics, ground reaction forces, electrical activity of muscles, and the level of perceived discomfort were recorded. The center of mass (COM), center of pressure (COP), and trunk displacements as well as the magnitude and latency of muscle activity of lower limb muscles were calculated during STS and compared to quantify the movement asymmetry. Discomfort on the left and right side of the body (thigh and feet) induced statistically significant displacement of the trunk towards the opposite side. There was statistically significant asymmetry in the activity of the left and right Tibialis Anterior, Medial Gastrocnemius, and Biceps Femoris muscles when discomfort was induced underneath the left side of the body (thigh and feet). The technique was effective in causing asymmetry and promoted the use of the contralateral side. The outcome provides a foundation for future investigations of the role of discomfort-inducing devices in improving symmetry of the STS in individuals with unilateral impairment.